2021
DOI: 10.12659/aot.933354
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative Low-Dose Dexmedetomidine Administration Associated with Reduced Hepatic Ischemia-Reperfusion Injury in Pediatric Deceased Liver Transplantation: A Retrospective Cohort Study

Abstract: Background Dexmedetomidine (DEX) attenuates hepatic ischemia-reperfusion injury (HIRI) in adult liver transplantation (LT), but its effects on postoperative liver graft function in pediatric LT remain unclear. We sought to investigate whether intraoperative DEX administration was associated with improved liver graft function in pediatric LT recipients. It was hypothesized that DEX administration was associated with reduced HIRI and improved liver graft function. Material/Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…No new clinical trial was found after searching the clinical trial registration platform ClinicalTrial.gov and WHO ICTRP. Finally, nine studies were included in the meta-analysis, with a total of 648 participants ( Choi et al, 2016 ; Fayed et al, 2016 ; Sayed and Yassen, 2016 ; Xu et al, 2016 ; Lee et al, 2020 ; Lee et al, 2021 ; Ustun et al, 2021 ; Zhang et al, 2021 ; Zhang et al, 2022 ). See Figure 1 for the combined search results.…”
Section: Resultsmentioning
confidence: 99%
“…No new clinical trial was found after searching the clinical trial registration platform ClinicalTrial.gov and WHO ICTRP. Finally, nine studies were included in the meta-analysis, with a total of 648 participants ( Choi et al, 2016 ; Fayed et al, 2016 ; Sayed and Yassen, 2016 ; Xu et al, 2016 ; Lee et al, 2020 ; Lee et al, 2021 ; Ustun et al, 2021 ; Zhang et al, 2021 ; Zhang et al, 2022 ). See Figure 1 for the combined search results.…”
Section: Resultsmentioning
confidence: 99%
“…In accordance with the present results, Fayed and colleagues demonstrated that an intraoperative infusion of DEX at 0.8 µg/kg/h could exert hepatoprotective effects against HIRI in adult living-related LT recipients, as shown by an improved liver graft function, better histopathological scores, and decreased ICAM-1 levels ( 6 ). A recent retrospective study showed that intraoperative low-dose DEX was associated with reduced HIRI in pediatric deceased LT ( 10 ). Another ongoing randomized controlled trial (NCT03770130) is currently investigating the effects of intraoperative DEX compared to placebo on EAD and PNF in adult deceased LT ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, researchers from the Tianjin First Center Hospital have demonstrated that intraoperative DEX administration protected against myocardial, kidney, and brain injuries in pediatric living-related LT ( 7 – 9 ). More recently, Zhang and colleagues ( 10 ) observed that intraoperative low-dose DEX administration was associated with reduced HIRI in pediatric deceased LT. However, mixed results have been reported in the literature ( 11 13 ), and some researchers ( 11 ) failed to detect a benefit of perioperative DEX infusion on postoperative cognitive dysfunction in adult living-related LT.…”
Section: Introductionmentioning
confidence: 99%
“…As a highly selective a 2 -receptor agonist, dexmedetomidine (DEX) is widely used in clinical anesthesia for satisfactory sedation and analgesia without causing respiratory depression and hemodynamic instability (7). Moreover, animal and human studies have reported that DEX is effective in preventing postoperative delirium, promoting liver regeneration, inhibiting sepsis-induced systemic inflammatory response and injury, and improving the functions of important organs such as the kidney, lung, intestinal tract, and heart postoperatively or in the intensive care unit (ICU) (8)(9)(10)(11). Several fundamental experiments have proved the protective effects of DEX on liver function after surgery by demonstrating that perioperative DEX use significantly reduced inflammatory response and oxidative stress injury in hepatectomy or liver transplantation surgeries (12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%